2011
DOI: 10.5005/jp-journals-10080-1431
|View full text |Cite
|
Sign up to set email alerts
|

All Internal Bone Transport: Use of a Lengthening Nail and Double Plating for Management of Femoral Bone Loss

Abstract: Background Variety of techniques for management of segmental femoral bone loss have been described, each with different advantages and challenges during treatment. The development of motorized lengthening nails has provided a potential for all internal bone transport, avoiding some of the difficulties with external fixation in the femur. At present, there is limited published literature on experiences in this technique. Aim The development of this technique aimed to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…2 AP (a, b, c) and lateral (d, e, f) radiographs of Patient 3 showing the defect at the start, during the retrograde bone transport and at the final stage. This demonstrates plate bending, as seen in two of our patients post-tumour resection while Wright et al [13] and Barinaga et al [11] reported exclusively traumatic bone loss. Any differences have not been clearly detected and stated, but it is conceivable that a bone tumour pathology would result in longer follow-up due to the additional use of adjuvants.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…2 AP (a, b, c) and lateral (d, e, f) radiographs of Patient 3 showing the defect at the start, during the retrograde bone transport and at the final stage. This demonstrates plate bending, as seen in two of our patients post-tumour resection while Wright et al [13] and Barinaga et al [11] reported exclusively traumatic bone loss. Any differences have not been clearly detected and stated, but it is conceivable that a bone tumour pathology would result in longer follow-up due to the additional use of adjuvants.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, Olesen et al [ 12 ] treaded on the same boundary with a mean femoral defect of 9.3 cm (range 7–11.5) and a mean tibial defect of 8.9 cm (range 4.8–15). Wright et al [ 13 ] reported a mean femoral defect size of 10.3 cm (range 7–16). Barinaga et al [ 11 ] reported on a traumatic tibial fracture of 3.0 cm when PABST was indicated, after previous IM nail failure when the initial defect was 4.2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations